Conceitos e discursos da educação inclusiva e especial: políticas públicas e a formação continuada dos professores o curso AEE Surdos- UFU - Moraes, Bruna Lorena Barbosa (2019)
This research is a qualitative and exploratory bibliographic investigation of how the concepts of normality, abnormality, inclusion and rights to schooling of the special ducation public were historically constructed and treated in the discourse of ducational inclusion. In addition to identifying and analyzing how these discourses appear in public policies of continuing education for teachers and documents that guide this training, it discusses the conceptual issue of the public of special education aiming at the inclusive school proposal. To this end, it was analyzed the continuing education course of the National Network of Continuing Education in Special Education offered in 2018, reinforced or refuted these conceptual issues. The main policies that cover inclusive and special education were analyzed, in parallel with the analysis of the material adopted in the training course, as well as the analysis of the questionnaires applied at the beginning and end of the course in question. For this, we use discourse analysis as a methodological analysis tool, adopting Foucaultian studies as a reference on the conceptual issue of norm, discourse and biopower. It was possible to make the historical construction of how the concepts involving inclusive and special education and how they were carefully constructed and disseminated, mainly through public policies. This dissertation is in line with the State, politics and management of education, with the study it was possible to infer that the course in question takes an approach in this perspective, causing teachers in the process of continuing education moments of reflection on the subject. However, it is also emphasized that more investments are needed in the continuing education of teachers, so that the issue of conceptualization, especially regarding normality, is the object of daily reflection.